CLSM anatomy of internal genitalia of Mackiella reclinata n. sp. and systematic remarks on eriophyoid mites from the tribe Mackiellini Keifer, 1946 (Eriophyoidea: Phytoptidae) - Chetverikov, Philipp E.; Craemer, Charnie; Vishnyakov, Andrey E.; Sukhareva, Sogdiana I. (Zootaxa, 2014)
A new mackielline mite, Mackiella reclinata n. sp., from a South African indigenous palm-tree, Phoenix reclinata, is described in detail using different microscopy techniques. A CSLM study of M. reclinata n. sp. internal genitalia shows that mites of this genus possess teardrop shaped spermathecae, sausage-like spermathecal tubes directed anteriad and a subtrapezoidal anterior genital apodeme with a peculiar apical plate, orthogonal to the anterior-posterior body axis. Pairwise angles between the spermatheca, spermathecal tube and the longitudinal bridge of M. reclinata n. sp. females were measured. The angle between the spermathecal tube and longitudinal bridge is a quite stable morphometric character and thus is considered to be appropriate for comparison of different eriophyoid taxa. LTSEM and CLSM study shows that M. reclinata n. sp. possesses a unique, broadened frontal lobe of the prodorsal shield comprised of apical and basal parts entirely covering the dorsal palpcoxae. The incompletely described mite species Mackiella borasis Mohanasundaram, 1981 does not conform to the diagnosis of Mackiella and herein is transferred to the subfamily Phytoptinae incertae sedis.